Political Party Endorsement in Supporting the Sole Candidate Muhammad Fadhil Arief and H. Bakhtiar in the 2024 Simultaneous Regional Election of Batanghari Regency - Hatta Abdi Muhammad; Sutri Destemi Elsi; Cholillah Suci Pratiwi; Nasuhaidi Nasuhaidi; Arissy Jorgi Sutan (Greenation International Journal of Law and Social Sciences, 2026)
This study analyzes the political party endorsement strategies leading to the sole-candidate scenario in Batanghari Regency during the 2024 simultaneous regional elections and its implications for democratic quality. While existing literature largely focuses on multi-candidate competition, a significant research gap remains regarding the specific mechanisms of "political cartels" that eliminate local opposition. Using a qualitative case study approach with NVivo 12 Plus, the research identifies that strategic alliances (44.83%), resource considerations (31.03%), and electability (24.14%) were the primary drivers of unanimous endorsements. The findings demonstrate that this "Three-Actor Framework" transforms elections into referendum-style contests, driven by public perception (41.38%) and elite dominance (34.48%) rather than ideological alignment. This research contributes to the field by offering a novel analytical model of how institutional fragility and pragmatic coalition-building, specifically the prioritization of short-term success (41.38%) over cadre development (24.14%), effectively neutralize electoral competitiveness. The study concludes that the "cartelization" of local parties erodes democratic resilience, suggesting an urgent need for regulatory reforms to restore pluralism.